Firm quality or market sentiment: What matters more for IPO investors? - Neupane, Suman; Paudyal, Krishna; Thapa, Chandra (Journal of Banking & Finance, 2014)
This paper investigates the investment decisions of IPO investors when equipped with information on both the quality of the firm and the market sentiment. Unique regulatory provisions allow IPO investors in India to have access to the independent assessment of firm quality and information on the participation of other investors, including institutional investors. At the same time, an active grey market reveals market sentiment before the application for subscription is closed. The results, which are robust to alternative model specifications, suggest that the institutional investors’ decision is guided almost exclusively by firm quality while the retail investors’ decision to participate in IPOs is strongly influenced by market sentiment, even in a highly transparent market where both sets of information are freely available.